Short-Term Contracting and Strategic Oil Reserves - Clifford, Norman; Crawford, Vincent P. (Review of Economic Studies, 1987)
The effect of short-term contracting on resource extraction is studied, in a two-country model of international trade in oil. Countries' planners are assumed to be fully rational, with perfect information and perfect foresight. Contracts are assumed perfectly enforceable and complete, except that short-term contracts do not allow commitments to actions taken beyond the contract period. We show that short-term contracting limits countries' opportunities for intertemporal consumption-smoothing, reducing their collective tolerance for temporal variation in consumption. This tends to make them extract more slowly than in the efficient plan that results from long-term contracting.